Effective and safe solar lentigo treatment with frequency doubled Nd:YAG (532) laser - our experiences - Kecelj, Nada (LAHA (Online ed.), 2020)
In retrograde study we analysed 33 patients, who were treated for solar lentigo with StarWalker - frequency doubled Nd:YAG (532) laser. By telephone interview after an average one and half year after last therapy, the questionnaires were completed. 4 men and 29 women with average 61 years (min. 32 years, max. 85 years) were included. 20 patients had laser treatment of face lentigines, 3 of dorsal hands and 10 of both hands and face together. 20 subjects received one and 13 subjects received two treatment sessions. The treating doctor evaluated final results after frequency doubled Nd:YAG (532) laser treatment of lentigo by comparing the photo documentation of involved patients before and at least 3 weeks after the laser therapy. Comparing to previous reports we used lower energy, lower frequency, bigger spot, and less repetitions for good result of lentigo treatment. One pass was applied using 4 mm or 5 mm spot size, 1,0-1,5 J/cm2 fluence, and 1- 2 Hz frequency. Sun protection was advised. Majority of 33 included patients admitted, that recovery time was not longer than two weeks, laser therapy and recovery time to complete healing was not painful, the laser therapy of solar lentigines was safe and both patients and treating doctor were very satisfied with the result of the treatment. In conclusion, we find treatment of solar lentigines of our patients with StarWalker - frequency doubled Nd:YAG (532) laser safe, not painful and long-time effective.
Keywords: dermatologija; dermatology; frekvenčni podvojeni laser; frequency doubled laser; solar lentigo; sončni lentigo